Coupling of defect-clusters in a linear chain-identical defects - Srivastava K.P.; Ojha S.P. (My University, 2025)
A numerical study on the coupling of two identical defect-clusters of light atoms embedded in a linear chain of heavy atoms taking second neighbour interaction into account has been made. The efficacy of the rule established by Rosenstock and McGill for the determination of defect frequencies has been discussed. On the basis of the present study a method has been suggested for computing defect frequencies very accurately. © 1979.